Neural Correlates of Psychotherapeutic Treatment of Post-traumatic Stress Disorder: A Systematic Literature Review - Malejko, Kathrin; Abler, Birgit; Plener, Paul L.; Straub, Joana (Frontiers in Psychiatry, 2017)
Objectives: Posttraumatic stress disorder (PTSD) is a common psychiatric disease with changes in neural circuitries. Neurobiological models conceptualize the symptoms of PTSD as correlates of a dysfunctional stress reaction to traumatic events. Functional imaging studies showed an increased amygdala and a decreased prefrontal cortex response in PTSD patients. As psychotherapeutic approaches represent the gold standard for PTSD treatment, it is important to examine its underlying neurobiological correlates. Methods: Studies published until august 2016 were selected through systematic literature research in the databases PubMed, PsychInfo and Cochrane Library’s Central Register of Controlled Trials or were identified manually by searching reference lists of selected articles. Search terms were “neural correlates” OR “fMRI” OR SPECT”, AND “therapy” AND “PTSD”. 19 articles were included in the present review whereof 15 studies compared pre-to-post therapy signal-changes, six studies related pre-treatment activity to pre-to-post symptom improvement and four studies compared neural correlates of responders versus non-responders. The disposed therapy forms were cognitive behavioral therapy (CBT), Eye movement desensitization and reprocessing (EMDR), cognitive therapy, exposure therapy, mindfulness-based intervention, brief eclectic psychotherapy and unspecified therapy. Results: Successful psychotherapy of PTSD was repeatedly shown to be accompanied by decreased activity in the amygdala and the insula as well as increased activity in the dorsal anterior cingulate cortex (dACC) and hippocampus. Elevated dACC activity prior to treatment was related to subsequent treatment success and a positive predictor for treatment response. Elevated amygdala and insula pre-treatment-activities were related to treatment failure. Discussion: Decreased activity in limbic brain regions and increased activity in frontal brain areas in PTSD patients after successful psychotherapeutic treatment might reflect regained top-down-control over previously impaired bottom-up processes.